Colorectal cancer survivorship: A systematic review and thematic synthesis of qualitative research - Lim, Chloe Yi Shing; Laidsaar‐Powell, Rebekah Clare; Young, Jane M.; Kao, Steven Chuan‐Hao; Zhang, Yuehan; Butow, Phyllis (European journal of cancer care, 2021)
Introduction With rapid changes in treatments for colorectal cancer (CRC), qualitative research into CRC survivorship requires greater synthesis. This paper aims to fill this gap through a systematic review (PROSPERO CRD42019131576) and thematic synthesis of the qualitative literature on survivorship experiences across early‐stage and advanced CRC survivors. Methods CINAHL, Embase, MEDLINE, PsycINFO and PubMed were searched for qualitative CRC survivorship papers. Titles, s and full texts were screened. Included articles (n = 81) underwent data extraction, CASP qualitative bias ratings and thematic synthesis. Results Bowel dysfunction caused functional limitations and negative quality of life (QoL), while stomas posed threats to body image and confidence. Physical symptoms hindered return to work, increasing financial burdens. Survivors’ unmet needs included information regarding symptom expectations and management, and ongoing support throughout recovery. Advanced and early‐stage survivors shared similar experiences. Advanced survivors struggled with fear of cancer recurrence/progression and feelings of powerlessness. Functional limitations, financial impacts and sexuality in advanced survivors were underexplored areas. Conclusion CRC and its treatments impact survivors’ QoL in all areas. A coordinated supportive care response is required to address survivors’ unmet needs. Future qualitative studies should explore advanced CRC subpopulations, treatment‐specific impacts on QoL and long‐term (>5 years) impacts on CRC survivors.